2021
DOI: 10.1097/ju.0000000000001945
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Preoperative Immunonutrition on Perioperative Outcomes following Cystectomy

Abstract: Study Need and Importance: Radical cystectomy (RC) for the management of muscle-invasive bladder cancer remains a morbid procedure with high rates of perioperative complications. 1,2 The role of preoperative immunonutritional supplementation (pre-INS) in improving post-RC outcomes is promising and needs further validation. 3e5 What We Found: We performed a retrospective review of 204 patients who underwent RC for bladder cancer at a single institution, comparing patients who received oral L-arginine-based pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 21 publications
(51 reference statements)
1
12
1
Order By: Relevance
“…[7][8][9][10] In 2021, Khaleel et al reported in a relatively large number of cases (n = 204) that intake of IMPACT for 5 days before surgery signi cantly reduced postoperative infectious complications after radical cystectomy and urinary diversion. 11 Our study also showed that preoperative intake of IMPACT signi cantly reduced the incidence of SSI.…”
Section: Discussionsupporting
confidence: 63%
“…[7][8][9][10] In 2021, Khaleel et al reported in a relatively large number of cases (n = 204) that intake of IMPACT for 5 days before surgery signi cantly reduced postoperative infectious complications after radical cystectomy and urinary diversion. 11 Our study also showed that preoperative intake of IMPACT signi cantly reduced the incidence of SSI.…”
Section: Discussionsupporting
confidence: 63%
“…28 Preoperative immunonutrition has also been shown to promote a lower overall inflammatory state by correcting the Th1-Th2 balance, as well as decreasing the need for postoperative total parenteral nutrition. 29,30 Understanding when to give immunonutritional therapy in the context of RC is yet to be answered and requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, preoperative oral arginine and n-3 fatty acid supplementation has been shown to improve the immunometabolic host response and outcome after colorectal resection for cancer, showing decreased infection rate, and improved gut oxygenation and microperfusion [ 101 ]. L-arginine supplementation and other immunonutritional support has also been shown to decrease infection rates and lower inflammatory response in radical cystectomy patients [ 102 , 103 ]. As of now, there is no defined standard of care for immune-nutritional supplementation during cancer treatment.…”
Section: Future Applications Of Halpmentioning
confidence: 99%